Characterization of Green-Synthesized Reduced Graphene Oxide using Aloe vera Extract and Its Application for Surface Water Treatment - Dwiria Wahyuni; Mega Nurhanisa; Ya’ Muhammad Arsyad; Mia Audina (Jurnal Penelitian Pendidikan IPA, 2025)
Reduced graphene oxide (rGO) is a carbon-based material with high surface area and chemical stability, making it an effective adsorbent for water purification. This study investigates the green synthesis of rGO using Aloe vera extract as a natural reducing agent and its application in treating surface water from the Kapuas River, Indonesia. Graphene oxide was reduced with Aloe vera extract under varying time conditions, and the resulting rGO samples were characterized to confirm the reduction process. The structural and compositional analyses revealed that increasing reduction time enhanced oxygen removal and improved surface morphology. The application tests showed that rGO substantially improved water quality: color decreased from 225 to 95 PCU (57.8% reduction), turbidity dropped from 16.2 NTU to 1.2 NTU (92.4% removal), and dissolved iron concentration decreased from 0.65 ppm to 0.37 ppm (43.07% removal), with pH remaining stable near 6.5. Among all samples, rGO reduced for 120 minutes achieved the highest purification efficiency. These findings demonstrate the feasibility of Aloe vera-reduced rGO as a sustainable adsorbent for surface water purification.